Pengaruh Pendekatan Saintifik Melalui Model PBL Terhadap Kemampuan Berpikir Kritis Siswa Pada Mata Pelajaran Fikih Kelas XI IPA di MAN 1 Pasaman Barat - Dewita, Resma; C, Charles; A, Afrinaldi; Dewi, Yelfi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The inadequate critical thinking skills of children in education spurred this study. Therefore, a scientific method is one of the learning strategies required to help pupils to acquire their critical thinking abilities. One learning model capable of supporting a scientific approach is the PBL model. This study thus seeks to determine the extent of effect the "Scientific Approach Through the For the Fiqh Class XI Science Subject at MAN 1 West Pasaman,"PBL Model tests students' critical thinking ability". Here is quantitative study using correlational techniques. There are ninety-five pupils in total, three courses. There were 95 students in the sample; the method of sampling was complete sampling. Data was gathered via a questionnaire and subjected to a basic linear regression test. It may be concluded that the scientific method applied using the PBL model has a favorable influence on critical thinking abilities and Ha is accepted because the sig. equal to 0.001 < 0.05 and t_count value 4.545 > t_table 1.980. Furthermore, the scientific method used via the PBL paradigm affects critical thinking abilities by 18.2%; the remaining 81.8% is formed by additional elements not investigated in this study.